Antibiotic administration via indwelling peritoneal catheter to treat infected malignant ascites. Issue 11 (17th October 2022) - Jayawardena, Thisuri; Vekaria, Sona; Krivinskas, Sophie; Sidhu, Calvinjit; Chakera, Aron; Lee, Y. C. Gary
Abstract: Indwelling pleural catheter is an established management for malignant pleural effusions. Extending its use to patients with malignant ascites by insertion of a catheter intraperitoneally enables regular outpatient drainage and improves quality‐of‐life. However, indwelling pleural/peritoneal catheter (IPC/IPeC) is associated with catheter‐related infections, traditionally managed with systemic antibiotics and occasionally requires catheter removal. Direct administration of antibiotics intra‐abdominally via peritoneal dialysis (PD) catheters is a well‐established, efficacious practice in PD‐related peritonitis and minimizes systemic adverse effects. We applied the same principles to a patient with peritoneal mesothelioma who developed peritonitis 3 weeks after insertion of IPeC. Intraperitoneal vancomycin was administered via, and compatible with, the IPeC. The patient tolerated the treatment without adverse effects and made a full recovery without requiring catheter removal. Abstract : Indwelling pleural and peritoneal catheters improve quality of life in patients with malignant pleural effusions and ascites. However, they are associated with catheter‐related infections, traditionally managed with systemic antibiotics. We present a patient with peritoneal mesothelioma who developed Staphylococcus aureus peritonitis three weeks after indwelling catheter insertion and successfully treated with intraperitoneal vancomycin directly to the site of infection.